Animal models of cerebral amyloid angiopathy (CAA) - Hernández Guillamon, Mar (Henry Stewart Talks, 2023)
Cerebral amyloid angiopathy (CAA), Beta-amyloid, Vascular amyloid deposition, Transgenic rodent models, Naturally occurring CAA models, Interventional models, Cerebral microhemorrhages, Smooth muscle loss, CAA biomarkers